Divulgação científica em 140 caracteres: o Twitter institucional a FAPEAM - Tomás, Renata Nobre (2013)
With the coming of the internet, there were major changes in the way we access information. In the field of scientific divulgation, many institutions have found new ways of communicating by using the www molds. In addition to traditional media, we now have websites and portals, electronic journals, discussion forums and even social networking profiles. An example of that is the increasing use institutions have been doing of Twitter – instant and concise tool that has been used for teaching and research institutions to promote research produced by them. This study aims, therefore, to analyze how the scientific divulgation discourse is constituted in a discursive genre that emerges in this context of valorization of the internet – the tweet – a genre where messages cannot exceed 140 characters. To compose our corpus, we selected 12 months of institutional Twitter posts from the Foundation of Support for Research of the State of Amazonas – Fundação de Amparo à Pesquisa do Estado do Amazonas (FAPEAM) – which amounted 1378 tweets. To support our research, we mainly based in: Bueno (1985, 2007, 2009, 2010 and 2012), Zamboni (2001) and Orlandi (2001), to treat the boundaries between science discourse and the discourse of scientific divulgation; Bourdieu (1983 and 2001), to address the conflicts within those two fields; Bakhtin (2003) and Marcuschi (2008), to characterize how the tweet from the scientific sphere is constituted as a discoursive genre and how it is configured regarding the compositional construction, style and thematic content; Bakhtin/Volochínov (2009), AuthierRevuz (1998 and 2004) and Maingueneau (1996 and 1997), to address the relevance and the constitution of the discourse of authority for science communication. We found that in addition to the compositional structure fixed to 140 characters – the most stable characteristic in the tweet – other parts of its structure are an avatar image to the left side of the text, and icons with some additional information below the message, providing greater ease in the inclusion and access of devices, images, sound and videos. As for style, for belonging to the sphere of science journalism, it presents simple and objective language, sentences in direct order, use of the third person singular, predominant cultural norms and use of few adjectives. Despite being short texts, the use of contracted of words, emoticons and Internet language is rare. The thematic content, in turn, is different from the one in personal, journalistic and even some institutional profiles. The FAPEAM twitter addresses issues related to science and technology, prevailing general news about research, events and invitations to tender documents. The customer service and the surveys are also recurrent. Most of the posts have a link, which generally leads to a news story on the homepage of the foundation itself. Regarding the reported speech, it was found in 19.6% of the posts, with the predominance of retweets and direct speech.